Nano Liposome: Tools for Target Drug Delivery - Ray, Biswaranjan (Technological Innovation in Pharmaceutical Research Vol. 8, 2021)
Liposomes are nano size artificial vesicles of spherical shape that can be produced from natural phospholipids and cholesterol. Liposomes are defined as spherical Micro- or Nano-sized particles that contain an internal water pool surrounded by a bilaminar membrane. The building blocks of the membrane are phospholipid molecules or a combination of phospholipids with sterols, such as cholesterol, or with other surface -active ingredients. Liposomes are nano-scale spheroid vesicles composed of one or multiple lipid bilayer (s) enclosing an aqueous core. Liposomes can be manufactured using several methods, including thin-film hydration, reverse phase evaporation, and microfluidic mixing. Liposomal preparation reduce the roughness because of its interaction with corneocytes, the intracellular lipid resulting in skin softening and smoothing. Various liposome based products for facial and body care, make-up, mascara & foundation, haircare, sunscreen products & perfumes are in market.